2012
DOI: 10.1007/s00345-012-0989-8
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer detection rates in different biopsy schemes. Which cores for which patients?

Abstract: The addition of 4 lateral peripheral samples did not increase the CDR of the 10-core biopsy scheme. The addition of four paramedian peripheral samples was beneficial only in patients with PSA density <0.15, in whom the 10-core scheme would have miss almost 16 % of tumors. Since more than half of our patients had low (<0.15) PSA density, these findings seem to be of great clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 16 publications
0
19
0
2
Order By: Relevance
“…In addition, it should be pointed out that in this study we used a TRUS-guided biopsy with an extended 10-core biopsy scheme as previously described. 13,14 Although we have shown that the addition of 4 lateral peripheral samples did not increase the cancer detection rate of the 10-core biopsy scheme, 15 it is well known that with this approach it exists the possibility of undersampling the prostate, especially in the anterior and apical areas. These regions are well recognized as being difficult to sample with a transrectal approach.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, it should be pointed out that in this study we used a TRUS-guided biopsy with an extended 10-core biopsy scheme as previously described. 13,14 Although we have shown that the addition of 4 lateral peripheral samples did not increase the cancer detection rate of the 10-core biopsy scheme, 15 it is well known that with this approach it exists the possibility of undersampling the prostate, especially in the anterior and apical areas. These regions are well recognized as being difficult to sample with a transrectal approach.…”
Section: Discussionmentioning
confidence: 80%
“…Following local anaesthesia, 13,14 TRUS was used to determine prostate volume and to guide transrectal prostate sampling according to our systematic 18-core biopsy scheme. 15 …”
Section: Introductionmentioning
confidence: 99%
“…However, only about 30–40% of men with abnormal PSA values or physical exam findings are routinely diagnosed with PC on transrectal ultrasound guided biopsy 53 . Recent studies have evaluated germline PC-risk SNPs to predict PC diagnosis on biopsy in men of European ancestry 54, 55 and different racial populations 5658 .…”
Section: Germline Prostate Cancer Risk Variants and Biopsy Resultsmentioning
confidence: 99%
“…Since a limited number of cores might not decrease the chance of obtaining the small foci and it was desirable to avoid adverse effects, in the present study the biopsies were performed via the perineal route, collecting ≥12 biopsy cores, depending on prostate volume [18]. The perineal route is advantageous compared to the rectal route because it reduces the likelihood of missing some foci [19].…”
Section: Discussionmentioning
confidence: 99%